Advances in the Prevention and Management of Obesity and Eating Disorders - Amanda Sainsbury (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Obesity and eating disorders remain major public health concerns worldwide that often co-exist. While we are far from having definitive solutions, scientific insights into the prevention and management of obesity and eating disorders have developed significantly in recent years. This research has been stimulated by the continuous challenge of reducing the global burden of obesity and its commonly associated health complications, as well as the life-threatening characteristics of eating disorders. Looking towards better solutions for these pressing public health concerns, this book addresses recent scientific findings regarding the prevention and management of obesity and eating disorders. It reports on cognition and mental health in people with obesity, as well as on food addiction, co-morbidities of eating disorders, cultural aspects of eating, intermittent dietary energy restriction as a treatment for overweight or obesity, factors influencing the adherence to dietary treatments for overweight and obesity, philosophies underpinning dietary practices, treatment of eating disorders in men, cognitive remediation therapy for anorexia nervosa, and online or virtual interventions for weight management or bulimia nervosa. This book includes culturally diverse findings from research groups around the world (e.g. Australia, UK, Norway, Brazil), and is informative for healthcare professionals and researchers working in the fields of obesity and/or eating disorders.